Low-cost Point-of-Care Biosensors Using Common Electronic Components as Transducers - Han, Yong Duk; Chun, Hyeong Jin; Yoon, Hyun C. (Biochip Journal, 2020)
Although vast research has been performed on biosensors, the materialization of low-cost point-of-care (POC) biosensors exhibiting portability, user-friendliness, and highly reliable analytical performance has not yet been achieved. The utilization of electronic/optoelectronic components and devices as signal transducers is being studied as a promising approach for the development of ideal POC biosensors, owing to their remarkable advantages including robust optoelectronic properties, cost-effectiveness, low-bulkiness, and flexibility in applications. This review summarizes recent notable innovations in the development of POC biosensors, in terms of transducers. Specifically, the application of optoelectronic components (e.g., diode-lighting components and semiconductor imaging sensors) and electronic devices (e.g., flatbed scanner, bio/physical sensor, and smartphone) in biosensors is described.
Keywords: Analytical performance; Electronic component; Electronic device; Optoelectronic components; Optoelectronic properties; Point of care; Semiconductor imaging; Signal transducers; Biosensor; Optoelectronic components; Point-of-care; Smartphone-based sensor; Transducer